Pengaruh Pembelajaran Daring Terhadap Motivasi Belajar Siswa SD - Aldo Putra Pratama (Universitas Muhammadiyah Enrekang, 2021)
The background of this research is related to the higher demand of the learning process during the Covid-19 Pandemic. The education workforce is required to be creative and innovative so that the Online Learning process can be carried out properly. As the consequentes of all the limitations and challenge, the Online Learning process still need to be maximized more. Due to that problems the students seems to experience the lack of Learning Motivation. The purpose of this research is to find out how much the Online Learning influences the elementary student’s learning motivation. This study uses a Document Study of the results of previous research, the author also uses the Meta Analysis method. The data collection technique was done by examining the Google Schoolar. From the search results, the author analyzed 3 articles. Based on the analysis, it depicted tha Online Learning can decrease the elementary student’s learning motivation. Before Online Learning the average of student learning motivation is 80,8% and after Online Learning the average has decreased to 64,01%. In conclusion, the student’s learning motivation decrease until 16,07%.